Amitav Ghosh. - Mondal, Anshuman A. (Contemporary world writers., 2007)
Amitav Ghosh is an authoritative critical introduction to the fictional and non-fictional writings of one of the most celebrated and significant literary voices to have emerged from India in recent decades. It is the first full-length study of Amitav Ghosh's work to be available outside India. Encompassing all of Ghosh's fictional and non-fictional writings to date, this book takes a thematic approach which enables in-depth analysis of the cluster of themes, ideas and issues that Ghosh has steadily built up into a substantial intellectual project. This project overlaps significantly with many o.